Measures of Urbanisation and Interrelationship between Factors Thereof in Tiruchirapalli District: A SEM Analysis - , E. Gayathri; , K. Sita Devi (Archives of Current Research International, 2024)
Urbanization is a complex socio-economic process that transforms the built environment, converting formerly rural into urban settlements, while also shifting the spatial distribution of population from rural to urban areas. Urbanization was an important driving force in migration and commuting, because urban areas offer many economic opportunities to rural people through better jobs, new skills and cultural changes. The specific objective formulated for the study are to find out the various measures of urbanisation in the study area and to develop a structural equation model for depicting the interrelationship between these factors of urbanisation. A multistage random sampling technique was adopted. The tools of analysis for the study are Principal Component Analysis (PCA), Confirmatory Factor Analysis (CFA) using Structural Equation Model (SEM). The results revealed that the variables in the study had effect on urbanisation and the recommended fitness models and reliability test were achieved the required level for the study. The study concluded that the urbanisation has influence on the factors such as cropping pattern, land use pattern, growing employment and rural-urban migration in the study area.